Hypothyroidism and metabolic cardiovascular disease - Patrizio, Armando; Ferrari, Silvia Martina; Elia, Giusy; Ragusa, Francesca; Balestri, Eugenia; Botrini, Chiara; Rugani, Licia; Mazzi, Valeria; Antonelli, Alessandro; Fallahi, Poupak; Benvenga, Salvatore (Frontiers in Endocrinology, 2024)
Cardiovascular disease (CVD) remains the leading cause of death worldwide, representing a major health issue of social and economic relevance. Both hyperthyroidism and hypothyroidism are very common in the adult population, and both disorders may contribute to the onset and progression of CVD. After a brief description of the role of thyroid hormones (TH) on the physiology of cardiovascular system and the potential mechanism that link TH alterations with changes in cardiac function, blood pressure, endothelial function and lipid levels, we review updated data about the clinical impact of Overt Hypothyroidism (OH) and Subclinical Hypothyroidism (SCH) on CV risk, CVD and mortality. Furthermore, we summarize the current evidence for treating SCH with levothyroxine (L-T4). Several guidelines of distinguished endocrine societies recommend treatment for SCH with TSH higher than 10 mIU/L, where the benefit of L-T4 therapy is more evident for younger people, but still controversial in those aged over 65 years. Based on current knowledge, more research efforts are needed to better address the clinical management of CV risk and CVD in the elderly affected by SCH.